Transmedia experiences that blur the boundaries between the real and the fictional world - Gouveia, Patrícia (2021)
This chapter uses an arts- and design-based research methodology to explore emergent possibilities in contemporary transmedia arts and design practices. Focusing in narrative and fiction creation for the development of participatory and performative events with emphasis in audience or community engagement and conveying inspiration from modernist and postmodernist movements, it reveals the role of participation design in connected and smart experiences for urban cooperative gaming and play. Mobile gaming and play technologies taking advantage of sensors and data tracking devices immerse us in a persistent and pervasive game of life which blur the boundaries between the real and the fictional world